Molecular markers and their application to cassava breeding: past, present and future - Ferguson, Morag E.; Rabbi, Ismail Y.; Kim, D.J.; Gedil, Melaku A; Becerra López Lavelle, Luis Augusto; Okogbenin, Emmanuel (Springer, 2012)
The advent of relatively low-cost, massively parallel, high-throughput genome sequencing and the resultant availability of high density markers are revolutionizing the ways in which molecular markers can be applied to plant breeding. With the availability of the draft cassava genome sequence, the cassava community is poised to take advantage of these new tools. Here we review the development of molecular markers applied to cassava breeding and describe the achievements that have been made using predominantly simple sequence repeat (SSR) markers. At this time of change, we report on the curation of 3,367 published and unpublished SSR primer pairs and provide a non-redundant database. We also describe ways in which new tools, particularly single nucleotide polymorphism (SNP) markers, can be applied to the development of high density maps and to fine mapping, association mapping, gene discovery, transcript profiling, inbred line development and the prediction of heterosis, gene mining in wild species and introgressions, and genome-wide approaches, including marker-assisted recurrent selection (MARS) and genomic selection (GS). Where applicable we describe how these tools are already being applied for amassing genetic gain in cassava.